2023
DOI: 10.1093/jpp/rgac102
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol alleviates sepsis-associated cardiac dysfunction via attenuating inflammation, apoptosis and oxidative stress

Abstract: Objective Honokiol, a natural active compound extracted from Chinese herbal medicine, can ameliorate acute lung and kidney injury of sepsis. This study was to explore the effects of honokiol on sepsis-associated cardiac dysfunction and the underlying mechanism. Methods Septic mice were induced by cecal ligation and puncture (CLP) or lipopolysaccharide (LPS), and septic HL-1 or AC16 cells were induced by LPS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…40 Increasing pieces of evidence demonstrated that cardiomyocyte apoptosis is involved in the pathogenesis of sepsis-induced cardiac dysfunction and inhibiting apoptosis could improve cardiac function. [41][42][43][44] Bcl-2 regulates the mitochondrial pathway of apoptosis, also known as intrinsic apoptosis pathway. 45 Bcl-2 was proved to protect cells against programmed cell death.…”
Section: Discussionmentioning
confidence: 99%
“…40 Increasing pieces of evidence demonstrated that cardiomyocyte apoptosis is involved in the pathogenesis of sepsis-induced cardiac dysfunction and inhibiting apoptosis could improve cardiac function. [41][42][43][44] Bcl-2 regulates the mitochondrial pathway of apoptosis, also known as intrinsic apoptosis pathway. 45 Bcl-2 was proved to protect cells against programmed cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study has several promising findings, several limitations should be acknowledged. First, There is mounting evidence that overproduction of ROS plays a critical role in the regulation of SMD [ 48 , 49 ]. Although we showed that NLRP3 mediated pyroptosis and inflammation contribute to SMD in the current study, whether Apelin attenuates SMD via regulation of ROS production warrants investigation.…”
Section: Discussionmentioning
confidence: 99%